Javanese Indigenous Knowledge in The Collections of Suaka Budaya Keraton Kasunanan Surakarta Museum - Nurislaminingsih, Rizki; Bakry, Gema Nusantara; Ganggi, Roro Isyawati Permata; Christiani, Lidya (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2024)
Kasunanan Surakarta is one of the kingdoms in Java that has inherited various cultural products. The proof is the collection stored in the Suaka Budaya Keraton Kasunanan Surakarta Museum. These cultural product objects are proof of the existence of indigenous Javanese ancestral knowledge. Therefore, this research aims to identify local knowledge based on museum collections. The results of this research show that Javanese people have the knowledge to weave bamboo into geometrically shaped containers and the health benefits of traditional cooking utensils. They can also make traditional machines (lesung, lumpang, and alu) for making flour, breaking seed shells, and grinding spices. Other skills include making traditional communication tools (lumpang, gamelan, and bells), traditional games (to train children in learning to master emotional intelligence, strategies for getting things and investing), traditional sports (for learning about war and choosing soldiers), and blacksmith (keris and spear). They are also experts in making fermented foods, potions for skin and hair beauty (ratus), and oral health (kinang). They also master the field of performing arts with the musical instruments rebab, dance and wayang (suket and klithik). The conclusion is that the Javanese people have local knowledge in the fields of handicrafts, post-harvest agricultural equipment, communication tools, games, sports, blacksmithing, fermented foods, beauty, dental and oral health, and performing arts.